Do residents support night tourism in the historic district? the case of Wuhu Ancient City - Cao, Chaoyi; Ramachandran, Sridar; Siow, Mayling; Subramaniam, Thanam; Lulu, Liu (Routledge, 2024)
The study was to establish a framework that integrates sense of place, involvement, perceived costs and benefits of night tourism impact, and support for night tourism development was developed based on Social Exchange Theory (SET). In Wuhu Ancient City, a historic district well-known for its night tourism, a questionnaire survey was carried out, 306 valid questionnaires received. The findings showed that while perceived costs of night tourism impact have a negative influence on night tourism development support, perceived advantages of night tourism impact had a favorable impact. Perceived costs and benefits of the impact of night tourism, support for the development of night tourism as well, were influenced by sense of place. On the other hand, involvement had no bearing on the support for the development of night tourism; rather, it simply affected the perceived costs and advantages of the impact. Additionally, from the standpoint of local support, the study suggests and countermeasures for the development of night tourism in historic district. © 2024 Informa UK Limited, trading as Taylor & Francis Group.